2004
DOI: 10.1088/0022-3727/37/11/013
|View full text |Cite
|
Sign up to set email alerts
|

Applications of a broadband electron-beam pumped XUV radiation source

Abstract: A simple table-top windowless system for extreme ultraviolet (XUV) spectroscopy which avoids differential pumping for both the radiation source and the detector is presented. The radiation source uses excimer emission from rare gases excited with low energy (13 keV) electron beam. Broadband emission in the entire wavelength range from 60 to 140 nm is demonstrated using He, Ne and a Ne-Ar gas mixture. It was observed that the so-called third continuum is absent in Ne when low energy electron-beam excitation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…These two components consequently have (nearly) the same wavelength. The loss of spectral information of the scintillation light in the measurement, however, might influence this intensity ratio: for example, for the case of neon in the gas phase it has been shown that the third excimer continuum 3 only appears for the excitation with heavy ions, but not for the excitation with electrons [11]. As light emission in this continuum is also very fast, see Sect.…”
Section: Introductionmentioning
confidence: 99%
“…These two components consequently have (nearly) the same wavelength. The loss of spectral information of the scintillation light in the measurement, however, might influence this intensity ratio: for example, for the case of neon in the gas phase it has been shown that the third excimer continuum 3 only appears for the excitation with heavy ions, but not for the excitation with electrons [11]. As light emission in this continuum is also very fast, see Sect.…”
Section: Introductionmentioning
confidence: 99%
“…[9] and [5] in the context of vacuum ultraviolet light sources. (1) is sent into the target chamber (2) through a very thin (300nm) SiN/SiO2 membrane (3). The microwave electrode (4) is mounted on the opposite side.…”
Section: Experimental Setup 21 Conceptmentioning
confidence: 99%
“…However, this paper focuses on measurements performed at atmospheric pressure. Operating the electron beam sustained discharge in a continuous mode offers enough time to record high quality optical emission spectra of the plasma with a scanning monochromator over a very broad spectral range from about 60nm [3] up to 1000nm.…”
Section: Introductionmentioning
confidence: 99%
“…Rate constant Reference and comments k 1 4.4ϫ 10 −32 6 mass spectroscopy k 2 3.3ϫ 10 −8 T e −0.43 → 1.6ϫ 10 −7 7 used in kinetic model 3.7ϫ 10 −8 ͑0.027/ T g ͒T e −0.43 → 1.7ϫ 10 −7 3 used in kinetic model k 3 1.3ϫ 10 −10 8 selected ion flow 1 ϫ 10 −10 7 used in kinetic model k 4 4.1ϫ 10 −34 9 laser absorption 5 ϫ 10 − 34 10 used in kinetic model 1.6ϫ 10 − 34 3 used in kinetic model k 5 5.5ϫ 10 −11 11 crossed beams k 5 + k 6 6 ϫ 10 −11 3 used in kinetic model k 6 1.5ϫ 10 −11 3 calculated using kinetic model k 7k 8k 9k 10 1 ϫ 10 −10 ͑ =2͒ 12 quantum mechanical 4.5ϫ 10 −15 ͑ =1͒ 12 2.5ϫ 10 −20 ͑ =0͒ 12 k 11 2.08ϫ 10 −9 13 ion cyclotron ͑2.1− 2.5͒ ϫ 10 −9 13 polarization theory k 12 0.9ϫ 10 −9 14 mass spectroscopy k 13 1 ϫ 10 −8 15 merged beams 2 ϫ 10 −7 ͑all ͒ 16 merged beams…”
Section: Reactionmentioning
confidence: 99%
“…Combining experimental techniques of time-resolved spectroscopy using pulsed electron-beam excitation 4 and extreme ultraviolet ͑EUV͒ spectroscopy, 5 we were able to study the time dependence of light emission following short pulse ͑5 ns͒ lowenergy electron-beam excitation. Combining experimental techniques of time-resolved spectroscopy using pulsed electron-beam excitation 4 and extreme ultraviolet ͑EUV͒ spectroscopy, 5 we were able to study the time dependence of light emission following short pulse ͑5 ns͒ lowenergy electron-beam excitation.…”
Section: Introductionmentioning
confidence: 99%